Influencing shower behaviour using real-time feedback and goal-based messaging - Nicklin, Harry; Jeffrey, Paul; Smith, Heather M. (Elsevier, 2026)
Showering is among the most resource intensive activities in terms of household water and energy consumption. Reducing both water and associated energy consumption, which continues to be stubbornly high in many jurisdictions, calls for changes in behaviour. Using real-time data feeds via automatic shower timers (n=336) installed in individual showers on a university campus and providing five forms of messaging inspired by the Capability - Opportunity – Motivation – Behaviour (COM-B) behaviour change framework, we analysed the impacts of selected interventions on shower durations over a four-month experimental period. Results of ANOVA and mixed effect regression models comparing treatment groups to a control demonstrate that the group with just an automatic shower timer took shorter showers. Goal-based messaging did not strengthen the impact of the shower timer, except in the case of a message regarding the energy footprint of each minute in the shower which was associated with shower durations 30% shorter than the control at the beginning of the experiment, and 15% when averaged throughout the period of the experiment. Findings challenge assumptions about the effectiveness of new water saving technologies and enrich our understanding of the limits of using smart sensors. We are also able to comment on the relative contributions of the COM-B model elements and augment elements of habit discontinuity theory.
Keywords: 41 Environmental Sciences; 4104 Environmental management; Behaviour change; Data feedback; Goal-setting; Household water use; Smart sensors